Whey waste as potential feedstock for biohydrogen production. (December 2016) - Patel, Anil Kumar; Vaisnav, Neha; Mathur, Anshu; Gupta, Ravi; Tuli, Deepak Kumar
Abstract: In-house isolate Clostridium sp . IODB-O3 was exploited for biohydrogen production using cheese whey waste in batch fermentation. Analysis of cheese whey shows, it is enriched with lactose, lactic acid and protein components which were observed most favourable for biohydrogen production. Biohydrogen yield by IODB-O3 was compared with the cultures naturally occurring in waste solely or in combinations, and found that Clostridium sp . IODB-O3 was the best producer. The maximum biohydrogen yield obtained was 6.35 ± 0.2 mol-H2 /mol-lactose. The cumulative H2 production (ml/L), 3330 ± 50, H2 production rate (ml/L/h), 139 ± 5, and specific H2 production (ml/g/h), 694 ± 10 were obtained. Clostridium sp . IODB-O3 exhibited better H2 yield from cheese whey than the reported values in literature. Importantly, the enhancement of biohydrogen yield was observed possibly due to absence of inhibitory compounds, presence of essential nutrients, protein and lactic acid fractions which supported better cell growth than that of the lactose and glucose media. Carbon balance was carried out for the process which provided more insights in IODB-O3 metabolic pathway for biohydrogen production. This study may help for effective utilization of whey wastes for economic large scale biohydrogen production. Graphical abstract: Highlights: Whey found to be best substrate for BioH2 production by in-house isolate IODB-O3. Clostridium sp . IODB-O3 exhibited better BioH2 yield than the whey-native flora. Maximum biohydrogen yield obtained was 6.35 ± 0.2 mol-H2 /mol-lactose. H2 yield exhibited by IODB-O3 was better than the reported values in the literature.